Analysis of Work Posture and Improvement of Worker Activities at a Four-Wheeled Vehicle Lighting Company - Imansuri, Febriza; Ardiansyah, Muhammad; Irhannudin, Muhammad; Rahimun, Farhan Bagus; Priandi, Fajar Putra; Pratama, Indra Rizki; Wulansari, Isma (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
PMG, Ltd is a company that manufactures and subcontracts for car lighting companies.The problem on the automobile lamp factory floor is that workers do repetitive operations and lifting loads manually without using tools. The goal of this research is to determine the risk level of work posture and provide recommendations for improvements to four-wheeled vehicle lighting component companies. The methods used to assess operator working posture are the Nordic Body Map (NBM), Quick Exposure Check (QEC) and Ovako Working Posture Analysis System (OWAS) questionnaires. Based on the results of the NBM questionnaire, Musculoskeletal Disorder (MSD) symptoms were found on the neck, back, hands and feet. The score for the QEC method is 65.43%, which means further research and changes are needed, and the OWAS method is in category 2, which means that corrective action is needed in the near future. Improvements in working posture were carried out by redesigning the work table according to anthropometric ergonomics principles and reducing the flow of stages in the lamp production process from 11 steps to 8 work steps.